Trade Integration and the Prospects for Rural Enterprise Development in China. - Park, A (OECD, 2001)
The rapid growth of China’s rural industrial sector has been a main engine for growth during China’s economic reform. From 1985 to 1998, TVE output value increased by more than six times in real terms. Productivity growth of China’s collectively owned firms has consistently outpaced that of state-owned firms, and collective firms sustained moderate productivity growth even through the mid-1990s when productivity growth in the state sector turned negative. The share of gross industrial output accounted for by nonstate firms increased from 22 to 72 percent from 1978 to 1998, with the size of the non-state sector (measured by output) surpassing the state-owned sector in 1994. TVEs, here defined to include all rural enterprises, including private firms, created 107 million new jobs from 1978 to 1996, the year in which employment peaked at 135 million in 1996, equal to 28 percent of rural labour and 20 percent of the national labour force. This rapid growth of rural industry, in addition to its direct effects on growth, also contributed to China’s overall economic performance by putting competitive pressure on SOEs, financing the provision of local public goods, and facilitating the rapid transfer of “surplus” agricultural labour to non-agricultural activities with higher levels of productivity.